Analysis Of The Influence Of Promotional Media Types And Product Diversity On Consumer Purchase Decisions At Tiket.Com Online Travel Agent - Ricky Kurniaji Purnomo; H. Akhmad Saufi (Experimental Student Experiences, 2022)
This study aims to determine the effect of Promotional Media Types and Product Diversity on Consumer Purchase Decisions at the online travel agent Tiket.com. The population in this study were all users of the Tiket.com OTA service, while the sample in this study were 110 users of the Tiket.com service using a purposive sampling technique. This type of research is associative research. Data processing in this study used SPSS 25.0 for Windows, where validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, significance test (t test) and coefficient of determination test (R2) were carried out. Based on the research results show that: (1) the type of promotional media has a significant effect on consumer purchasing decisions. (2) product diversity has a significant effect on consumer purchasing decisions. For further research it is recommended to conduct research outside of the independent variables that have been used in this study, or to combine several variables that have been used in this study, such as the type of promotional media and product variety with other variables that can influence consumer purchasing decisions.